PERANCANGAN PRINT AD IKLAN LAYANAN MASYARAKAT TENTANG BAHAYA PENGGUNAAN EARPHONE BAGI TELINGA DAN OTAK - FADIL, Henra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Technological developments such as the Earphones are increasingly in demand among teenagers and adults. However, the danger caused by the use of earphones is less known by the target audience.The purpose of this design is designing a public service advertisement about the dangers of using earphones for the ears and brain on the educative and effective print ad media in an effort to sensitize Earphone users to be wiser in using earphones.The method used uses visual communication design theory, data collection, books, media information, illustrations, colors, layouts and typography. The results of this design are public service announcements about the dangers of using earphones for the ears and brain in Print Ad media. Print advertising (Print Ad) is the development of printing media that is able to attract attention and provide an alternative, especially for teenagers and adults to read it. The design of Print Ad as the main media is also supported by several media such as T-Shirts, Tote Bags, X-Banners, Pamphlets, Stickers and Pins which are useful as supporting main media and as a promotional media.Keywords : Danger Earphones, Public Service Announcements, Print Ad